Self-Assembly of Polymers - Vikulina, Anna (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Nowadays, polymer self-assembly has become extremely attractive for both biological (drug delivery, tissue engineering, scaffolds) and non-biological (packaging, semiconductors) applications. In nature, a number of key biological processes are driven by polymer self-assembly, for instance protein folding. Impressive morphologies can be assembled from polymers thanks to a diverse range of interactions involved, e.g., electrostatics, hydrophobic, hots-guest interactions, etc. Both 2D and 3D tailor-made assemblies can be designed through modern powerful techniques and approaches such as the layer-by-layer and the Langmuir-Blodgett deposition, hard and soft templating. This Special Issue highlights contributions (research papers, short communications, review articles) that focus on recent developments in polymer self-assembly for both fundamental understanding the assembly phenomenon and real applications.